2007
DOI: 10.1038/nature05843
|View full text |Cite
|
Sign up to set email alerts
|

8-oxo-guanine bypass by human DNA polymerases in the presence of auxiliary proteins

Abstract: Specialized DNA polymerases (DNA pols) are required for lesion bypass in human cells. Auxiliary factors have an important, but so far poorly understood, role. Here we analyse the effects of human proliferating cell nuclear antigen (PCNA) and replication protein A (RP-A) on six different human DNA pols--belonging to the B, Y and X classes--during in vitro bypass of different lesions. The mutagenic lesion 8-oxo-guanine (8-oxo-G) has high miscoding potential. A major and specific effect was found for 8-oxo-G bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
246
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(262 citation statements)
references
References 19 publications
14
246
2
Order By: Relevance
“…The incorporation of 2'-deoxyribonucleotides opposite 8-OH-Gua by human DNA pol η was analyzed in vitro. Human DNA pol η incorporates dATP and dCTP opposite the lesion with comparable efficiencies, but proliferating cell nuclear antigen (PCNA) and replication protein A (RP-A) enhance the correct 8-OH-Gua bypass [25][26][27][28][29][30]. The mammalian replicative DNA pols α and δ are error-prone against 8-OH-Gua [27,28,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of 2'-deoxyribonucleotides opposite 8-OH-Gua by human DNA pol η was analyzed in vitro. Human DNA pol η incorporates dATP and dCTP opposite the lesion with comparable efficiencies, but proliferating cell nuclear antigen (PCNA) and replication protein A (RP-A) enhance the correct 8-OH-Gua bypass [25][26][27][28][29][30]. The mammalian replicative DNA pols α and δ are error-prone against 8-OH-Gua [27,28,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TLS DNA pols bypassed 8-OH-Gua in vitro [25][26][27][28][29][30][31][32][33][34]. Thus, to understand the mutagenesis and carcinogenesis processes by 8-OH-Gua, it is important to examine the contributions of the polymerases to the induction and suppression of the G:CT:A mutations caused by this lesion in living mammalian cells.…”
Section: -Oh-gua Is Highly Mutagenic and Induces G:ct:a Transversiomentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their relaxed catalytic sites that allow them to accommodate distorted DNA structures, TLS polymerases are highly error-prone when copying normal undamaged DNA. Although studies of TLS have been largely focused on polymerases of the Y family (together with Polζ), other enzymes, such as Polµ, Polλ and Polθ, have shown robust translesion activity in vitro [49][50][51] .…”
Section: Somatic Hypermutation and Dna Polymerasesmentioning
confidence: 99%
“…Together with cofactors replication protein A and proliferating cell nuclear antigen, Pol k is the mammalian polymerase most able to correctly incorporate dC opposite 8-oxoG [Maga et al, 2007]. It is also cell-cycle regulated; phosphorylation by S-Cdk (Cdk2 and cyclin A) protects Pol k from ubiquitin-dependent proteolysis and stimulates expression during S and G2 phases.…”
Section: Pol Kmentioning
confidence: 99%